Climate-resilient Urban Neighborhoods: Assessment of Urban Densification Scenarios in the Extreme Climate events - Turk,Suheyla (2025)
Growing population in Swedish cities and limited natural resources combined with climate change impacts led decision-makers to develop densification strategies in city planning. However, densification could come with several challenges including reduced green spaces, increased urban heat island effect and energy demand, as well as the lack of thermal comfort in buildings. Densification becomes even more challenging when considering the projected increase in the intensity and frequency of extreme climate events, such as heatwaves and cold snaps. In this study, seven densification scenarios (L shaped, O shaped buildings) based on the trade-offs between urban greenery (L-U-O shaped with green) and urban density (moderate, and high density) were developed considering the number of floors and urban streets. Using a real urban area in Stockholm as a case study (base case), the measures included modifications to existing buildings (considering building age, physical properties) and the addition of new constructions in open spaces. Furthermore, to evaluate their impact on the energy performance of urban neighbourhoods in Stockholm, the energy performance and indoor thermal comfort of the developed scenarios were assessed. The assessment was done against historical climate conditions using the Typical Meteorological Year (TMY) weather file and future climate data targeting 2069. Three future climate weather files covering typical and extreme conditions were synthesized (2040-2069), including Typical Downscaling Year (TDY), Extreme Warm Year (EWY), and Extreme Cold Year (ECY). The dynamic energy simulations were conducted using the EnergyPlus engine, and the building properties were retrieved from open-source GIS databases, and Swedish building codes. Existing buildings were grouped as construction before and after 1975 and 2000. Results show that extreme weather conditions have a significant impact on energy performance of buildings, indicating the importance of considering extreme climate conditions in conventional urban planning practices. Increasing urban density from 0,40 to 0,52 led to 18% drop in heating demand in comparison to base cases. Adding 22% green surface coverage had minimal impact on heating and cooling demand under moderate densification in all weather conditions except for heating demand in extreme cold years. Higher green area density led to cooling demand to reduce by 35% during EWY in high densification scenario. Finally, the advantages and disadvantages of various design solutions, measures, and densification scenarios were evaluated. The findings of this study can support more informed decision-making for architects, urban planners, and city authorities regarding densification strategies.
Keywords: Extreme climate events; urban densification; heating and cooling demand; urban microclimate; urban greenery